Reference material for near-bottom water ansd sediment samples from RV Meteor cruise M147 - Xu, Antao; Hathorne, Ed C; Scholz, Florian; Chen, Ling; Koschinsky, Andrea; Frank, Martin (In: Xu, A et al. (2025): Dissolved neodymium and hafnium isotopes and rare earth element data of near-bottom water samples from RV Meteor cruise M147 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986565, 2025)
Nd and Hf isotope compositions of secondary standard solution and reference materials for checking the external reproducibility
Keywords: Amazon estuary; Dissolved neodymium and hafnium isotope; GEOTRACES; Rare earth elements and yttrium; Surface sediment